Perceptions of women on sexuality, intimacy, andhealth-related quality of life during the COVID-19 epidemic (Journal of Health Sciences, 2024)
Introduction: The COVID-19 epidemic and its restrictions have affected all aspects of people’s lives, including health-related quality of life and, considering sexuality as an integral part of individual needs, also intimacy and sexuality. Therefore, the aim of this article was to investigate women’s sexual functioning and health-related quality of life assessment in Slovenian women in the reproductive period.Methods: An online survey with valid questionnaires (short form 36 [SF-36] and Female sexual function index [FSFI-19]) was conducted in January 2022. All research ethical measures were taken to ensure the integrity of the participants.Results: The FSFI scale score was 25.37 ± 8.29, 1.18 points above the cutoff point, indicating a higher risk of sexual dysfunction (26.55). The estimated prevalence of sexual dysfunction was 36.8%, with sexual desire being the most problematic area. The mean score on the SF-36 scale in our sample reached 73.52 ± 13.84 on a 100-point scale, with 0 representing the worst and 100 the best quality of life; fatigue (x̅ = 48.50) was the most problematic category. The results partly reflect the results of foreign studies, but we must be aware of cultural differences in the understanding of sexuality and keep in mind that some countries faced difficult circumstances during the COVID-19 pandemic and that social constraints were different in 2020 than in 2022.Conclusion: The epidemic affected the sexual function of women of reproductive age and their perception of (health-related) quality of life.